The let-7b-5p, miR-326, and miR-125a-3p are associated with left ventricular systolic dysfunction in post-myocardial infarction - Dantas-Komatsu, Raquel Costa Silva; Cruz, Marina Sampaio; Freire, Paula Paccielli; Diniz, Rosiane Viana Zuza; Bortolin, Raul Hernandes; Cabral-Marques, Otávio; Souza, Kamilla Batista da Silva; Hirata, Mario Hiroyuki; Hirata, Rosario Dominguez Crespo; Reis, Bruna Zavarize; Jurisica, Igor; Silbiger, Vivian Nogueira; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Acute ST-elevation myocardial infarction (STEMI) can lead to adverse cardiac remodeling, resulting in left ventricular systolic dysfunction (LVSd) and heart failure. Epigenetic regulators, such as microRNAs, may be involved in the physiopathology of LVSd. Objective: This study explored microRNAs in peripheral blood mononuclear cells (PBMC) of post-myocardial infarction patients with LVSd. Methods: Post-STEMI patients were grouped as having (LVSd, n=9) or not LVSd (non-LVSd, n=16). The expression of 61 microRNAs was analyzed in PBMC by RT-qPCR and the differentially expressed microRNAs were identified. Principal Component Analysis stratified the microRNAs based on the development of dysfunction. Predictive variables of LVSd were investigated through logistic regression analysis. A system biology approach was used to explore the regulatory molecular network of the disease and an enrichment analysis was performed. Results: The let-7b-5p (AUC: 0.807; 95% CI: 0.63–0.98; p = 0.013), miR-125a-3p (AUC: 0.800; 95% CI: 0.61–0.99; p = 0.036) and miR-326 (AUC: 0.783; 95% CI: 0.54–1.00; p = 0.028) were upregulated in LVSd (p < 0.05) and discriminated LVSd from non-LVSd. Multivariate logistic regression analysis showed let-7b-5p (OR: 16.00; 95% CI: 1.54-166.05; p = 0.020) and miR-326 (OR: 28.00; 95% CI: 2.42-323.70; p = 0.008) as predictors of LVSd. The enrichment analysis of the targets of these three microRNAs is associated with immunological response, cell-cell adhesion, and cardiac changes. Conclusion: LVSd alters the expression of let-7b-5p, miR-326, and miR-125a-3p in PBMC from post-STEMI, indicating their potential involvement in the cardiac dysfunction physiopathology and highlighting these miRNAs as possible LVSd biomarkers.